PENGARUH KEPEMILIKAN MANAJERIAL DAN LEVERAGE TERHADAP TAX AVOIDANCE DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL MODERASI - Rahmad, Syarif (JAAKFE UNTAN (Jurnal Audit dan Akuntansi Fakultas Ekonomi Universitas Tanjungpura), 2025)
This study aims to determine the impact of Managerial Ownership and Leverage on Tax Avoidance and the role of Company Size in moderating the relations between Managerial Ownership and Leverage on Tax Avoidance in the Manufacturing sector listed on the Indonesia Stock Exchange from 2017 to 2020. The samples of this study were 113 companies in the Manufacturing sector from 2017 to 2020. The data was obtained by multiple linear regression analysis and Moderated Regression Analysis (MRA) using SPSS 25. The leverage in this study was proxied by DER. The results of the study indicate that Managerial Ownership has an effect on Tax Avoidance. DER has no effect on DER. In addition to moderation, company size can strengthen the effect of managerial ownership and leverage on tax avoidance.